Optimisation of growth medium for the production of cyclodextrin glucanotransferase from Bacillus stearothermophilus HR1 using response surface methodology - Abd. Rahman, Roshanida; Md. Illias, Rosli; Mohd Ghazali, Mohd Nawawi; Ismail, Ahmad Fauzi; Hassan, Osman; Kamaruddin, Kamarulzaman (Elsevier Science B.V., Amsterdam, 2004)
Cyclodextrin glucanotransferase (CGTase) activity was observed when the bacterium was grown in the medium at various initial pH values, containing carbon, nitrogen, phosphorus and mineral salt sources at 50 oC for 24 h in the shake flasks. The optimisation of this growth medium was carried out using response surface methodology. The design contains a total of 32 experimental trials involving 10 star points and 6 replicates at the centre points. The design was employed by selecting sago starch, peptone from casein, K2HPO4, CaCl2 and initial pH as five independent variables in this study. The optimal calculated values of tested variables for maximal production of CGTase were found to be comprised of: sago starch, 16.02 g/l; peptone from casein, 20 g/l; K2HPO4, 1.4 g/l; CaCl2, 0.2 g/l and initial pH, 7.54 with a predicted CGTase activity of 14.20 U/ml. These predicted optimal parameters were tested in the laboratory and the final CGTase activity obtained was very close to the predicted value at 14.80 U/ml.